The Effectiveness of Binary Oppositions in Producing Literary Meaning in the Poetry of Abdul Qadir Rashid al-Nasir - Abbas, Abbas Kamel (Thi Qar Arts Journal, 2025)
Binary oppositions occupy a wide range of ancient and modern human knowledge and are considered among the most prominent topics of modern literary theory. They represent one of the essential principles of poetics that found a broad and significant place within the structuralist method, particularly after the achievements of the linguist Ferdinand de Saussure, whose work relied heavily on the principle of binary oppositions. They also became central to analytical studies of literary texts within the descriptive approach. This reference to the role of binary oppositions was not the first of its kind, as earlier rhetorical studies had already established their presence. Classical rhetoric, especially in the science of al-Badiʿ (ornamentation), was rich with binaries such as parallelism, antithesis, contradiction, and equivalence. However, these were confined to the ornamental and aesthetic aspects of expression. Modern poetic studies, by contrast, expanded the role of binary oppositions, granting them a wide semantic and functional dimension with significant impact. This research, therefore, aims to trace the effectiveness of binary oppositions and their role in constructing literary meaning in the poetry of Abdul Qadir Rashid al-Nasiri